MENGAKTUALISASIKAN NILAI-NILAI PANCASILA DALAM KURIKULUM PENDIDIKAN NASIONAL - Nadia Kezia Situmeang, Sri Wenni; Alberto Siagian, Syahrial (STKIP Subang, 2025)
This article examines how the national curriculum can implement Pancasila values. First, the curriculum must integrate Pancasila values into all aspects of learning. Pancasila education needs to be strengthened as a special subject where students are taught the core values of Pancasila. In addition, Pancasila values must also be socialized in an interdisciplinary manner. The national curriculum should integrate Pancasila values with other subjects such as math, science, Indonesian language and cultural arts. In any learning context, it is important to identify and relate Pancasila values to students' situations and problems so that they can see the meaning of these values in everyday life. In addition, learner-centered teaching methods should also be applied. Students should be encouraged to actively participate in learning, discussion and cooperation to understand and instill the values of Pancasila. This process can also include real experiences such as visits to historical sites or interactions with different communities so that students can relate the values of Pancasila to existing social realities.